Skrining fitokimia dan isolasi senyawa steroid/triterpenoid dari ekstrak n-heksana daun Pepaya (Carrica papaya L) - Cindy Widya Rosa Br Simarmata; Haris Munandar Nasution; M Pandapotan Nasution; Yayuk Putri Rahayu (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
In Indonesia, papaya plants are common in several areas, from Sabang to Merauke. As a tropical country, almost all corners of Indonesia have various shapes and different types of papayas. Papaya leaves (Carica papaya L.) contain tannins, alkaloids, flavonoids, terpenoids, and saponins which act as antiparasitics. This research aims to determine the results of the chemical compound groups found in papaya leaves (Carica papaya L.). To determine the characteristics of isolates from n-hexane extract of papaya leaves (Carica papaya L.) using UV and IR spectrophotometry. This research includes making simplicia from papaya leaves, then phytochemical screening, then simplicia characterization, then making extracts from papaya leaf simplicia, after that analysis of the extract using the thin layer chromatography (TLC) method, then isolation using column chromatography (KK), purity testing using Two-way thin layer chromatography (TLC) and the isolation obtained were identified using ultraviolet (UV) spectrophotometry and infrared (IR) spectrophotometry. The results of the characterization of the Carica papaya L Simplicia showed that the water content was 4%, the water-soluble essence content was 16.64%, the ethanol-soluble essence content was 11.6%, the total ash content was 9.88%, the ash content was 0. 66%, the results of the phytochemical screening of Carica papaya L., simplicial contain steroid/triterpenoid compounds, alkaloids, flavonoids, saponins, tannins. The results of the isolated analysis showed that the isolate obtained was a violet-colored steroid/triterpenoid compound. The isolate obtained was analyzed using UV light spectrophotometry, giving an absorbance at a wavelength of 207 nm, indicating that there was a chromophore group. The IR spectrophotometry results showed OH, aliphatic CH, and CH2 groups, CH3, C=O and CO.